Time-Varying Risk Premiums and the Output Gap - Cooper, Ilan; Priestley, Richard (Review of Financial Studies, 2009)
The output gap, a production-based macroeconomic variable, is a strong predictor of U.S. stock returns. It is a prime business cycle indicator that does not include the level of market prices, thus removing any suspicion that returns are forecastable due to a “fad” in prices being washed away. The output gap forecasts returns both in-sample and out-of-sample, and it is robust to a host of checks. We show that the output gap also has predictive power for excess stock returns in other G7 countries and U.S. excess bond returns.